Pelarangan Submarine Tailing Disposal di Berbagai Negara Serta Aksi Hukum yang Dapat Dilakukan - Kiswo, Windu (Indonesian Journal of International Law, 2005)
Submarine Tailing Disposal (STD) is waste disposal activity to the sea through pipelines. Recently, the documentation system becomes the main problem of STD implementation. It is very weak so it can not cover the unpredicted effect to marine environment and the possibility of STD implementation’s failure. In United States, prohibition of STD is regulated in Clean Water Act. It requires 2 (two) important matters that are implementation of the Best Available Technology (BAT) and New Source Performance Standard (NSPS). While Canada regulate it i Canadaian Federal Metal Mining Liquid Effluent Regulation (MMLER) and Canada’s Fisheries Act. Indonesia itself doesn’t have special regulation to prohibit STD. That is why Indonesia need to have a clear and strict regulation about STD. This article tries to describe the importance pf the regulation that prohibit STD.